2012
DOI: 10.1111/j.1468-0475.2012.00578.x
|View full text |Cite
|
Sign up to set email alerts
|

The Overall Effect of the Business Cycle on Crime

Abstract: This paper analyses the 13 business cycles since 1933 to provide evidence on the old question of whether recessions cause crime. Using data from the United States, we find that recessions are consistently associated with an uptick in burglary and robbery, and a reduction in theft of motor vehicles. There is no statistical association with homicide. These patterns are suggestive of the relative importance of the various channels by which economic conditions influence crime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…Empirical studies have found that the effect of real economic activity is different between different types of crimes. Property crimes, violence crimes, and sex crimes are countercyclical, while the reverse is true for economic crimes due to increasing opportunity during economic expansions (Bushway et al 2012;Krüger 2011;Povel et al 2007); for example, Detotto and Otranto (2012) have recently found that economic crimes, including bankruptcy frauds, display a sensitivity to macro-economic conditions. Overall, we could expect a negative relationship between changes in bankruptcies and changes in economic growth: bankruptcies increase during economic downturns and recessions and are reduced during economic upturns.…”
Section: Data and Variablesmentioning
confidence: 99%
“…Empirical studies have found that the effect of real economic activity is different between different types of crimes. Property crimes, violence crimes, and sex crimes are countercyclical, while the reverse is true for economic crimes due to increasing opportunity during economic expansions (Bushway et al 2012;Krüger 2011;Povel et al 2007); for example, Detotto and Otranto (2012) have recently found that economic crimes, including bankruptcy frauds, display a sensitivity to macro-economic conditions. Overall, we could expect a negative relationship between changes in bankruptcies and changes in economic growth: bankruptcies increase during economic downturns and recessions and are reduced during economic upturns.…”
Section: Data and Variablesmentioning
confidence: 99%
“…But the property crime point estimates are in the opposite direction and sometimes statistically significant (if not entirely robust), which under-measurement seems unlikely to explain. Additionally, other interventions at the individual level often push violence in a di erent direction from other crimes (Kling et al, 2005;Deming, 2011;Jacob and Lefgren, 2003), and changes in labor market and macroeconomic conditions seem to a ect property but not violent crime (Raphael and Winter-Ebmer, 2001;Bushway et al, 2012). So violence may just be di erent.…”
Section: Resultsmentioning
confidence: 99%
“…A "minus" is given if the post peak rate of change is less than the annual rate of change during expansion. If the business cycle has no impact on the series we expect a 50 % probability (Bushway et al (2012)) of both signs. The other test is a simple t-test of the hypothesis that the average of the growth rates of the respective time series is equal in recession and non-recession phases.…”
Section: Recession Phasesmentioning
confidence: 98%
“…Firstly, we follow the method applied by Bushway et al (2012) to analyze the cyclical behavior of crime and calculate the cumulated changes of the time series during a downswing from peak to trough. Here, each business cycle is treated as an independent experimental trial.…”
Section: Recession Phasesmentioning
confidence: 99%